Global Health Education for Youth: A Humanitarian Priority - Andrew John Macnab (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
There may not seem to be an obvious link between the focus of the three events this issue is recognizing. However, in the context of global health and the journals’ mission statement of “shaping a more resilient, inclusive & youth-empowered future” there is a connection. World Breastfeeding Week aims to raise awareness and encourage more women to breastfeed, International Youth Day focuses on an age group which includes ‘the parents of tomorrow,’ and Humanitarian day pays tribute to humanitarian workers who have given their lives and suffered injuries in the course of their work, including those actively campaigning for the rights of women and girls in the face of gender inequity. In this context, enabling more mothers to breastfeed would bring considerable health and social benefits, youth are key ‘target audience’ to engage and educate on the positive impact breastfeeding can have on their future infants’ lives, and a global humanitarian aim is to balance traditional social norms that favor gender inequity, including those that negatively impact the ability of mothers to breastfeed. Published: 30 August 2025.